2002
DOI: 10.1103/physrevlett.88.245506
|View full text |Cite
|
Sign up to set email alerts
|

Nematics with Quenched Disorder: How Long Will It Take to Heal?

Abstract: Nematics with quenched disorder have been repeatedly predicted to form glass phases. Here we present turbidity experiments and computer simulations aimed at studying glass key features such as dynamics and history dependence in randomly perturbed nematics. Electric field-cooling alignment has been employed to prepare samples in suitably oriented starting states. Remarkable remnant order and slow dynamics are found both by experiment and simulations, indicating that random disorder can, by itself, induce a nema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 21 publications
4
48
0
Order By: Relevance
“…4 Although it seems a quite general behavior, the connection between the glass-like 4 dynamics of confined LC's and the nature of the porous topology, surface interactions and confinement-induced quenched disorder effects remains challenging. 21,22,23,24 The individual molecular dynamics of confined LC's is also strongly modified. Dielectric relaxation spectroscopy has been extensively used since it allows one to probe the rotationallibrational dynamics of the dipolar molecules around their short axis as well as tumbling relaxation modes around the local nematic director.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although it seems a quite general behavior, the connection between the glass-like 4 dynamics of confined LC's and the nature of the porous topology, surface interactions and confinement-induced quenched disorder effects remains challenging. 21,22,23,24 The individual molecular dynamics of confined LC's is also strongly modified. Dielectric relaxation spectroscopy has been extensively used since it allows one to probe the rotationallibrational dynamics of the dipolar molecules around their short axis as well as tumbling relaxation modes around the local nematic director.…”
Section: Introductionmentioning
confidence: 99%
“…x-ray scattering [14,15], x-ray intensity fluctuation spectroscopy [16], static and dynamic light-scattering [9,10,11], and deuterium NMR [17] studies on the nematic to smectic-A (N -SmA) and the isotropic to nematic (I -N ) phase transitions of this system have shown that there are clear quenched random-field characteristics as well as finite-size scaling effects…”
Section: Introductionmentioning
confidence: 99%
“…In the simulations we mimic the FC and ZFC states by studying the evolution from an Aligned (AIC 0 , with all aligned spins) and a Random Initial Configuration (RIC 0 ) [11]. The corresponding equilibrated configurations, here after referred to as AIC and RIC states, respectively, are remarkably different [11]. In Fig.…”
mentioning
confidence: 99%
“…The value of P2 for these equilibrated states is generally overestimated because of finite-size effect and decreases with increasing lattice size [12] as shown in the inset of Fig.1. In the simulations we mimic the FC and ZFC states by studying the evolution from an Aligned (AIC 0 , with all aligned spins) and a Random Initial Configuration (RIC 0 ) [11]. The corresponding equilibrated configurations, here after referred to as AIC and RIC states, respectively, are remarkably different [11].…”
mentioning
confidence: 99%